ANALISA PERANCANGAN UI/UX APLIKASI ABSENSI BERBASIS MOBILE MENGGUNAKAN METODE USER CENTERED DESIGN - Aditya, Reinaldi; Kurniawati, Laela (Politeknik Bisnis Indonesia, 2024)
In the digital era, information systems play a crucial role in business operations, including in hospitals. Kartika Pulo Mas. Currently, employee attendance using fingerprints has several problems, such as long queues, identification difficulties, and high investment and maintenance costs. To overcome this problem, an online-based mobile attendance application was developed. However, the main challenge is UI/UX design that is less than optimal, thereby reducing user comfort and efficiency. The aim of this research is to design a User Interface for a mobile attendance application that suits user needs. This research uses the User Centered Design method, which consists of 4 stages, namely understanding the context of use (Understand context of use), specifying user requirements (Specify user requirements), designing design solutions (Design Solutions Process), and evaluating the design against user needs (Evaluate against requirements). Testing was carried out using the System Usability Scale method to meet user needs. The questionnaire distributed used a Likert scale and was answered by 21 respondents. The results of the design evaluation concluded that the final SUS score calculation result was that the average score obtained was 87.5, which is Grade A. This indicates that users are very satisfied with the mobile attendance application.